(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
Autores: Daron Acemoglou y James A. Robinson Editorial: Deusto. Año de Publicación: 2012. 589 págs. ISBN: 978-84-234-1266-2